Regulation of microtubule nucleation in glioblastoma cells by ARF GTPase-activating proteins GIT1 and GIT2 and protein kinase C - Sulimenko, Vadym; Dráberová, Eduarda; Sládková, Vladimíra; Sulimenko, Tetyana; Vosecká, Věra; Skalli, Omar; Dráber, Pavel (Cancer cell international, 2025)
BACKGROUND: G protein-coupled receptor kinase-interacting proteins (GITs) function as GTPase-activating proteins (GAPs) for small GTPases of the ADP-ribosylation factor (Arf) family. While GIT proteins (GIT1 and GIT2) regulate both cell migration and microtubule organization, their corresponding regulatory mechanisms in glioblastoma cells remain largely unknown. To further investigate their role in microtubule modulation, we examined the function of GITs in microtubule nucleation and the involvement of protein kinase C (PKC) in this process. METHODS: Glioblastoma cell lines with depleted GIT protein levels were generated using shRNA lentiviral vectors. The cellular localization of GITs was visualized by immunofluorescence microscopy, microtubule nucleation was analyzed using time-lapse imaging, and cell migration was assessed through a wound healing assay. Phosphomimetic and non-phosphorylatable variants of GIT2 were prepared by site-directed mutagenesis. Immunoprecipitation, pull-down experiments, and kinase assays in the presence of PKC inhibitors were used to study protein interactions. RESULTS: Both GIT1 and GIT2 associate with proteins of the γ-tubulin ring complexes (γTuRCs), the primary microtubule nucleators, and localize to centrosomes. Depletion of GIT2 enhances centrosomal microtubule nucleation and has a more pronounced, yet opposite, effect on this process compared to GIT1. In contrast, the depletion of both GIT1 and GIT2 similarly affects cell migration. The N-terminal ArfGAP domain of GIT2 associates with centrosomes, regulates microtubule nucleation, and is phosphorylated by PKC, which modulates this process. We identified serine 46 (S46) on the ArfGAP domain as a PKC phosphorylation site and demonstrated that phosphorylation of GIT2 at S46 promotes microtubule nucleation. CONCLUSIONS: We propose that GIT2 phosphorylation provides a novel regulatory mechanism for microtubule nucleation in glioblastoma cells, contributing to their invasive properties.
Keywords: Protein kinase C (PKC); G protein-coupled receptor kinase-interacting proteins (GITs); Glioblastoma cells; Microtubule nucleation; Centrosomes